Sustainable small ports: Performance assessment tool for management, responsibility, impact, and self-monitoring - Olli-Pekka Brunila; Vappu Kunnaala-Hyrkki; Tommi Inkinen (Journal of Shipping and Trade (JST), 2023)
This paper proposes a conceptual performance assessment tool for evaluating the environmental performance in small seaports. The developed tool is based and built based on a literature review. Ports, depending on their size, tend to have several sustainability and environmental management needs. However, especially small or cargo specialized ports do not often have sufficient resources to implement environmental effectiveness enhancing tools, even if they need them. This paper reviews international quality and environmental management tools, standards, and selected frameworks. These include International Organization for Standardization standards, and Global Reporting Initiative and Corporate Social Responsibility concepts. Because checklist type self-diagnosis solutions are the easiest to adopt, and universally most applicable, the proposed environmental performance measurement tool has four specific categories: (1) environmental management; (2) responsibility; (3) impact assessment; and (4) self-monitoring. The proposed tool allows the ports to assess whether their environmental management practices are comparable to more expensive standards and certificates. The paper concludes with a discussion on the limitations and challenges related to different port types and their specific needs.
Keywords: 650; Assessment tool; Environmental performance; Ports; Quality management